Exploring the role of electronic structure on photo-catalytic behavior of carbon-nitride polymorphs. (30th October 2020) - Datta, Sujoy; Singh, Prashant; Jana, Debnarayan; Chaudhuri, Chhanda B.; Harbola, Manoj K.; Johnson, Duane D.; Mookerjee, Abhijit
Abstract: A fully self-consistent density-functional theory (DFT) with improved functionals is used to provide a comprehensive account of structural, electronic, and optical properties of C3 N4 polymorphs. Using our recently developed van Leeuwen-Baerends (vLB) corrected local-density approximation (LDA), we implemented LDA+vLB within full-potential N th -order muffin-tin orbital (FP-NMTO) method and show that it improves structural properties and band gaps compared to semi-local functionals (LDA/GGA). We demonstrate that the LDA+vLB predicts band-structure and work-function for well-studied 2D-graphene and bulk-Si in very good agreement with experiments, and more exact hybrid functional (HSE) calculations, as implemented in the Quantum-Espresso (QE) package. The structural and electronic-structure (band gap) properties of C3 N4 polymorphs calculated using FP-NMTO-LDA+vLB is compared with more sophisticated hybrid-functional calculations. We also perform detailed investigation of photocatalytic behavior using QE-HSE method of C3 N4 polymorphs through work-function, band (valence and conduction) position with respect to water reduction and oxidation potential. Our results show γ-C3 N4 as the best candidate for photocatalysis among all the C3 N4 polymorphs but it is dynamically unstable at 'zero' pressure. We show that γ-C3 N4 can be stabilized under hydrostatic-pressure, which improves its photocatalytic behavior relative to water reduction and oxidation potentials. Graphical abstract: Pressure-mediated structural stability and significantly enhanced photocatalytic behavior of γ-C3 N4 . Image 1